PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DAMPAKNYA PADA LOYALITAS PELANGGAN USAHA KECIL MENENGAH MONSTER SHAKER CAFE - Taufik Kamaru dan Arni Kurniati (Jurnal Manajemen FE-UB, 2017)
Customer loyalty is a top priority in this research because of the increasingly sharp competition among the culinary business in Indonesia. The main thing for companies to survive, compete and dominate the market then the price should be appropriate and the quality of service should be improved. The culinary business should pay attention to the things that are considered important by the customer. In order for customers to be satisfied and not to switch to other similar companies. So this study aims to determine the effect of price and quality of service to customer satisfaction impact on customer loyalty Small Medium Enterprises Monster Shaker Cafe.          The data used in this study is primary data collected from questionnaires using Likert Scale 1-5 as much as 95 respondents with random sampling technique that has been disseminated and filled by the customer. Data processing method using path analysis method (Path Analysis) with the help of SPSS Version 23 analysis tool.The results showed simultaneously variable price, service quality and customer satisfaction have a positive and significant impact on customer loyalty. Partially indicate that there are positive and significant influence between price to customer satisfaction. There is a positive and significant influence between service quality to customer satisfaction. There is a positive and significant influence between price and customer loyalty. There is a positive and significant influence between the quality of service to customer loyalty.          There is a positive and significant influence between customer satisfaction with customer loyalty. Price indirectly affects customer loyalty through customer satisfaction. Quality of service indirectly affect customer loyalty through customer satisfaction. Keywords: Price Influence, Service Quality, Customer Satisfaction, and Customer Loyalty